EFEKTIVITAS PROGRAM PENCEGAHAN STUNTING DI PUSKESMAS OESAPA KECAMATAN KELAPA LIMA KOTA KUPANG - Sonyati, Nini; Lino, Maria M.; Oktavianto, Aspri Budi (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Stunting remains a critical public health issue with long-term repercussions on child growth and cognitive development. The Indonesian government has designated stunting reduction as a national priority, implementing various intervention programs at both central and regional levels. This study aims to evaluate the effectiveness of the stunting prevention program at Puskesmas Oesapa, Kelapa Lima District, Kupang City. A qualitative descriptive approach was employed, utilizing data collection techniques such as interviews, observations, and document analysis. The findings reveal that the stunting prevention program at Puskesmas Oesapa has demonstrated a moderate level of efficacy, assessed through key indicators such as program outreach, target precision, monitoring mechanisms, and goal attainment. However, several impediments persist, including constraints in human resources, limited community awareness regarding stunting, and economic factors that hinder optimal nutritional fulfilment. To enhance the program’s efficacy, strategic improvements are necessary, encompassing heightened community education, optimized monitoring frameworks, and cross-sectoral collaboration to reduce stunting prevalence in Kupang City substantially.